EUROPEAN ASPECT OF AZERBAIJAN’S FOREIGN POLICY - Рагімлі, М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The Republic of Azerbaijan’s state hood development process state and stages, the features of which are determined by the specifics of history, geographical, geopolitical, national, and cultural factors, are considered. The role of the nation-state as the only possible political institution that can defend national interests both within the country (in the economic, sociocultural, domestic political spheres) and in the international arena is highlighted. The growing role of the modern state in preserving its sovereignty in the era of the formation of a multipolar post-globalization world and the effective use of its own natural and other resources for the benefit of the citizens of their country is emphasized. Particular attention is paid to the relations of Azerbaijan as one of the countries of the South Caucasus with powerful geopolitical actors, with the European Unionin particular. The presence of the unresolved problem of the prolonged Armenian-Azerbaijani conflict, which is a threat to the national sovereignty of Azerbaijan, is brought up. The specifics of Azerbaijan’s relations with the European Union are explained, namely: on the one hand, the importance of Azerbaijan as a transit country and supplier of gas and oil resources of the Caspian basin to the EU, and on the other hand, constant pressure on the political leadership of Azerbaijan to force them to make structural political changes and steadily implement generally accepted in Western Europe, democratic principles and values. The gradual transformation of the policy of the European Union itself is emphasized in the sense of closer proximity to a realistic assessment of its relations with member countries, neighboring countries, and associate members.